Model analizy popytu na usługi motoryzacyjne w ujęciu makroekonomicznym - Pamuła, Jan (Wydział Prawa i Administracji UAM, 1984)
Problems of services, particularly automotive ones, becomes more and more topical and interesting both practically and theoretically speaking. It is apparent that a rapid growth of demand for services in Poland is not accompanied by a sufficient growth of their supply. Problems of automotive services require proper investigation of both theoretical and empirical character. The article attempts at the construction of econometric model facilitating studies on demand for automotive services in macroeconomic approach. It indicates at those economic demographic and social factors which inflence shaping of demand for the examined services. The study has thus a cognitive and systematic character. The empirical results presented are merely an illustration to the constructed models.
Model of the demand study for automotive services in macroeconomic approach